Sources and doses of organic substrates in the production of tamarind rootstock - costa, jose maria; pereira, Eduardo castro; camara, Francisco mickael; mendonça, Vander; farias, wagner; MENDONÇA, Luciana (Comunicata Scientiae, 2018)
In order to evaluate the performance of different organic sources, the composition of the substrate to produce rootstocks of tamarind and nutritional status, an experiment was carried out in the seedling nursery at the Universidade Federal Rural do Semi-Árido Mossoró, RN. The experimental design was a randomized complete block, in a 3x4 factorial design with four replications. The first factor consisted of three organic sources (bovine manure, goat manure and commercial organic compound) and the second factor of four ratios of these sources (0, 20, 40 and 60% v v-1) mixed with soil. As a control was used only soil were 12 treatments with 10 plants per plot, totaling 480 plants. Morphological and nutritional characteristics were evaluated. The goat manure source provided the best results for the evaluated morphological characteristics. The proportion of 40% of organic matter, regardless of the organic source added to the substrate, favored the better development of tamarind seedlings.